Manufacture of three-dimensional (3D) microcapsules through the use of multifunctional biomaterials - Antunes, Jéssica Alexandra Sá (2020)
Prostate cancer is one of the most commonly diagnosed malignancy and a leading cause of death among men worldwide. Currently, despite many advances in medicine, the current treatments for this neoplasia are mostly ineffective. The development of advanced in vitro disease models that can recapitulate human prostate tumors may revert this scenario by accelerating the pre-clinical discovery of new therapies which can realistically impact patients’ life span. Up to now, regulatory agencies recommend that anti-tumor drug screening should be performed in two-dimensional (2D) cell cultures for gathering preliminary pre-clinical data. However, these models fail to mimic key characteristics of in vivo human tumors including their spatial distribution, cell-cell contacts and nutrients/oxygen gradients. Moreover, these 2D models utterly fail to replicate tumors extracellular matrix (ECM) and cellular heterogeneity. These intrinsic limitations cause a number of false positive/negative results and provide a poor correlation with clinical trials data. To overcome these issues, in vitro 3D tumor models were proposed as valuable alternatives. Such platforms are able to reproduce various aspects of human solid tumors microenvironment, including gene expression patterns, 3D cell-cell interactions, necrotic core formation and drug resistance phenotypes. The research work developed within the scope of this dissertation describes the production of a novel 3D prostate cancer in vitro tumor model that mimics prostate cancer bone metastasis cellular heterogeneity and ECM microenvironment. The model is comprised of human prostate cancer cells (PC-3) and human osteoblasts, encapsulated in spheroidal-shaped hydrogel microparticles. Such cell-laden spheroidal microcapsules were assembled on a quasi-superhydrophobic surface by unitary droplet dispensing through U.V. mediated photocrosslinking of methacrylated hyaluronic acid and methacrylated gelatin blends. The obtained results show that spheroidal microtumors were reproducible in terms of morphology, size and number of encapsulated cells. The selected HA-MA/GelMA formulations present the deposition of calcium after 14 days, when compared to the monocultures, thus evidencing the importance of osteoblasts inclusion. The evaluation of cisplatin cytotoxicity in heterotypic co-cultures showed that 2.5% HA-MA-5% GelMA microgels have higher drug resistance than 5% HA-MA-5% GelMA Overall, the findings indicate that quasi SH are suitable for rapid, and solvent-free, manufacture of 3D prostate tumor in vitro models that may serve as testing platforms for the discovery of new therapies for prostate cancer